The Kushan Period And Its Place In The History Of The Peoples Of The Surkhan Oasis - Zubayda Yuldasheva (International Journal on Integrated Education, 2022)
This article analyzes the influence of the Hellenistic culture period can be felt even in the utensils and utensils made of pottery used for household and household needs and significant economic and cultural upsurge in Termez.